On Questioned Document Examination in Forensic Linguistics - Khachatryan, Robert (Armenian Folia Anglistika, 2015)
The overarching objective of this article is to contemplate on the significance of questioned document examination in forensic linguistics. Questioned document examination (QDE) is a forensic linguistics discipline pertaining to disputed documents and applying a variety of linguistic methods and tools to answer questions about a disputed document. More specifically, this article elaborates on the categorization of legal documents that are instrumental in the process of establishing the authenticity of documents in dispute.
Keywords: questioned document; questioned document examination (QDE); types of documents; legal documents